Efeito hepatoprotetor causado pelo 3-alquinil selenofeno contra o dano oxidativo induzido por agentes químicos em ratos - Wilhelm, Ethel Antunes (2009)
The liver presents extraordinary functional diversity, particularly in the control of energy production, immune defense and volemic reserve. The human being is exposed occupationally and in the environment to a variety of hepatotoxic compounds, such as the use of paints and their derivatives (2-nitropropane, 2-NP), chemical reagents (carbon tetrachloride, CCl4) and exposure to cigarette (2-NP). Therefore, it is interesting the study of therapies to prevent or even reverse the poisoning caused by these compounds. Considering that reactive oxygen species (ROS) have an important role in various diseases, especially in liver diseases, the use of antioxidant therapies should be considered. In this context, the heterocyclic compounds containing selenium in their structures have attracted the attention of researchers. Thus, this study investigated the antioxidant activity of 3-alkynyl selenophenes in models of oxidative damage in vitro and ex vivo in rats (Wistar, male, weighing 200-300g). A class of 3-alkynyl selenophene compounds with different substitutions was tested, with the objective to assess their antioxidant profile and their possible toxic effect in vitro. As a result, 3-alkynyl selenophenes had antioxidant activity, but this activity was dependent on the presence of terminal alkynes in the molecule or easy conversion to it. The possible toxic effect of 3-alkynyl selenophenes was evaluated through the activity of the enzyme δ-aminolevulinate dehydratase (δ-ALA-D) in vitro. The results showed that none of 3-alkynyl selenophenes inhibited the activity of this enzyme, suggesting that this class of compound did not present toxicity on this enzyme. From these results, selenophene h (compound that had the best antioxidant activity in vitro) was selected for the evaluation of its protective effect against oxidative damage induced by 2-NP and CCl4 (ex vivo). Selenophene h (25 mg/kg) protected against the increase of markers of liver damage (aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities) and oxidative stress induced by administration of 2-NP in rats. 2-NP induced microscopic changes, evaluated by histopathological inspections, that were protected by this compound. Selenophene h showed a protective effect against the increase of lipid peroxidation and inhibition of activity of δ-ALA-D in animals treated with 2-NP. Selenophene h protected against oxidative damage induced by CCl4 in rats. A single dose of CCl4 caused significant hepatotoxicity, evidenced by elevated plasma enzyme activity of AST and ALT, increased incidence of histopathological lesions, increased lipid peroxidation levels and the activity of Glutathione-S-transferase (GST), decreased levels of ascorbic acid and the activity of catalase and δ-ALA-D. In conclusion, 3-alkynyl selenophene protected from all these changes, confirming its hepatoprotective effect. Considering the results, we suggest that 3-alkynyl selenophene, an antioxidant, may be a useful therapy for the oxidative damage induced by 2-NP or CCl4 .